Clinical Predictors of Severe Dehydration in Pediatric Acute Gastroenteritis. A Clinical Study: Predictors of Severe Dehydration in Pediatric Gastroenteritis - USAMA, ALI; ABDULLAH, HAFIZ HAMMAD; SHABBIR, AHMAD; RAMZAN, HUSSAIN; ALI, MUHAMMAD RASHID (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Acute gastroenteritis ranks among the major problems of morbidity in children all over the world, and the most severe complication of this situation is severe dehydration. The early detection of predictable clinical factors is necessary to start management in time, particularly in resource-constrained environments. Objectives: The shortcoming procedure aims to identify clinical predictors of severe dehydration in children who present with acute gastroenteritis. Methods: This was a cross-sectional study of the clinical population of 100 children (aged 6 months to 12 years) with acute gastroenteritis who were presented to a tertiary care hospital. The patients were assessed with the detailed history and systematic clinical examination. The severity of dehydration was categorized as per the world health organization (WHO) criteria. Demographic factors, frequency of diarrhea and vomiting, and the significant clinical manifestations, such as sunken eyes, dryness of the mucous membranes, time of capillary refill, skin turgor, heart-rate, mental status, peripheral pulses, and urine output, were measured on structured proforma. The statistical analysis was done to identify relationships between clinical predictors and severe dehydration. Results: Out of 100 children, Dehydration was severe in 38% of them. Markedly poor skin turgor, prolonged capillary refill time (>2 seconds) was also found to be significantly related to severe dehydration, as well as, sunken eyes (92.1%), dry mucous membranes (86.8%), tachycardia (71%), and lethargy (55.2%). Children who had 8 or more episodes/day diarrhea and 5 or more diarrhea episodes/day vomiting also exhibited the increased risk of severe dehydration. Another good predictor was decreased urine output which was reported in 81.5% of children who were severely dehydrated. Conclusion: Significant clinical features of severe dehydration such as sunken eyes, delayed capillary refill, dry mucous membranes, and poor skin turgor are good predictors of severe dehydration in pediatric acute gastroenteritis. It is possible to use these available bedside cues to contribute to fast triage and prompt action, especially in resource-limited settings.